Alhagi maurorum Flower Extract Mediated Novel Synthesis of Gold Nanoparticles - Anita, Sehrawat R. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The aim of this study is to synthesize gold nanoparticles (AuNPs) from flower extract of Alhagi maurorum and aqueous gold chloride through a simple green route. Materials and Methods: AuNPs were synthesized by the reaction mixture containing freshly prepared flower aqueous extract and HAuCl4 solution. The reduction of Au3+ ions to AuNPs was monitored at different time intervals (0-180 min), at different concentration of chloroauric acid (0.1-2.0 mM), and at varying content of flower extract (1.0-25.0 ml). Characterization and storage stability of synthesized AuNPs were also noticed in this study. Results and Discussion: Optimization studies showed that 0.5 mM of chloroauric acid and lower amount (5.0 ml) of flower extract in 1:5 ratio facilitated maximum synthesis of AuNPs at an incubation period of 20 min. Transmission electron microscopic study revealed a size range of 12-24 nm and crystalline nature of biosynthesized AuNPs. The possible involvement of biomolecules in the formation of AuNPs was confirmed by Fourier transform infrared spectroscopy (FTIR) study. Stability of synthesized AuNPs showed only some microaggregates in the reaction mixture after 120 days which indicates the formation of highly stable AuNPs by a novel, simple, non-toxic, and eco-friendly route. Conclusions: Flower extract of A. maurorum could be used as an efficient green material for the rapid and consistent synthesis of AuNPs and their use as an antimicrobial agent in drug delivery system and in pharmaceutical and medical industry for the human welfare.